In-Situ Concrete Compressive Strength Assessment by Point Load Test - Achfas Zacoeb (Rekayasa Sipil, 2011)
The field application of point load test (PLT) for assessing a compressive strength of RC structures isdescribed in this paper. This method is relatively new in concrete testing, and use a smaller corespecimen in order to reduce and minimize the level of destruction. The structure that will be evaluatedby this method is a 53 years old RC bridge deck. The value of compressive strength (f’cc) is calculatedfrom in-direct relationship with point load index (Is). In this paper, the deterioration in RC bridge deckalso will be evaluated by visual inspection.